Analysis of Village Fund Use in Improving Community Welfare in Baebunta District North Luwu Regency - kelana, Ardian; Patra, Ketut; Ikbal, Muh. (International Journal of Management Science and Information Technology, 2025)
This study aims to determine and explain the influence of the use of village funds in improving community welfare in Baebunta District, North Luwu Regency. This study uses a descriptive quantitative approach using a questionnaire instrument for data collection. The population in this study was 150 Heads of Families with 5 villages determining the sample using the slovin formula so that the number of samples was 109 Heads of Families. The results of partial testing produced the variable of the influence of village funds having a significant influence on community welfare, thus it was concluded that the use of village funds in Baebunta District, North Luwu Regency greatly improved the welfare of its people.